2005
DOI: 10.1093/brain/awh412
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous sinus thrombosis in children: risk factors, presentation, diagnosis and outcome

Abstract: Neuroimaging and management advances require review of indications for excluding cerebral venous sinus (sinovenous) thrombosis (CSVT) in children. Our goals were to examine (i) clinical presentations of CSVT, (ii) prothrombotic risk factors and other predisposing events, (iii) clinical and radiological features of brain lesions in CSVT compared with arterial stroke, and (iv) predictors of outcome. We studied 42 children with CSVT from five European paediatric neurology stroke registries. Patients aged from 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
416
4
36

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(478 citation statements)
references
References 66 publications
22
416
4
36
Order By: Relevance
“…1,9 CSVT in our patient could have arisen from an interplay of dehydration, homocystinuria and anemia. Regular follow-up has been emphasized upon in order to detect recurrence of CSVT as well as development of other complications early.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…1,9 CSVT in our patient could have arisen from an interplay of dehydration, homocystinuria and anemia. Regular follow-up has been emphasized upon in order to detect recurrence of CSVT as well as development of other complications early.…”
Section: Discussionmentioning
confidence: 75%
“…Sé bire et al (2005) found that the incidence of pediatric CVST is at least 0.67 per 100,000 children per year. 1 We present an interesting case of a six-year old-boy with extensive CSVT who was diagnosed to be suffering from homocystinuria.…”
Section: Introductionmentioning
confidence: 99%
“…Two other cases one with HbSC and one with HbSS were reported as part of a registry of 42 patients with DVST [5]. A third case was reported in registry of 63 patients from North America [8].…”
Section: Discussionmentioning
confidence: 97%
“…Sickle cell disease (SCD) is increasingly recognized as a hypercoagulable state but has not been identified as a potential cause of cerebral dural venous sinus thrombosis (DVST) despite six well documented cases in the literature [1][2][3][4][5]. DVST often presents with nonspecific symptoms, the most frequent of which is severe headache, and the average delay from onset of symptoms to the diagnosis is 7 days.…”
Section: Introductionmentioning
confidence: 99%
“…47 The most common risk factors for CSVT are dehydration and prothrombotic disorders with others including infection, trauma, cancer/ chemotherapy, and systemic disease. 47,48,49 …”
Section: Risk Factors and Pathophysiologymentioning
confidence: 99%